Odpowiedzi

2010-03-02T09:16:02+01:00
Ad.a
(x+1)(x+2)=x2+2x+x+2=x2+3x+2
ad.b
(3a+4)(a-5)=3a2-15a+4a-20=3a2-11a-20
ad.c
(2t+1)(1-3t)=2t-6t2+1-3t=-6t2-t+1
ad.d
(3ab-7)(3-7ab)=9ab-21a2b2-21+49ab=-21a2b2+58ab-21
ad.e
(x-y)(5x+6y)=5x2+6xy-5xy-6y2=5x2+xy-6y2
ad.f
(x+5y)(7x-y)=7x2-xy+35xy-5y2=7x2+34xy-5y2
ad.g
(2x do potęgi 4 -y)(x do potęgi 4 +y)=2x16+2x4y-x4y-y2=2x16+x4y-y2
ad.h
(ab-a(2ab+6a)=ab-2a2b-6a2
ad.i
(7pr2+2r)(2pr2-7)=14p2r4-49pr2+4pr4-14r
1 4 1
2010-03-02T09:16:45+01:00
A) (x+1)(x+2)= x2+2x+x+2=x2+3+2
b) (3a+4)(a-5)=3a2-15a+4a-20=3a2-11a-20
c) (2t+1)(1-3t)=2t-6t2+1-3t=6t2-t+1
d) (3ab-7)(3-7ab)=9ab-21ab2-21+49ab=-21ab2+58ab-21
e) (x-y)(5x+6y)=5x2+6xy-5xy-6y2=5x2-6y2+1x2
f) (x+5y)(7x-y)=8x2-xy+45xy-5y2=8x2+44xy-5y2
2010-03-02T09:19:53+01:00
A) (x+1)(x+2)= x2+2x+x+2=x2+3x+2
b) (3a+4)(a-5)=3a2-15a+4a-20=3a2-11a-20
c) (2t+1)(1-3t)= 2t-6t2+1-3t=-t-6t2+1
Niestety musze juz leciec wiec wiecej narazie nie zrobie ;p